Sistem Pendidikan Boarding School dalam Peningkatan Pemahaman Pendidikan Agama Islam Mahasiswa Institut Agama Islam Al-Aziziyah Samalanga - Zulkhairi, Zulkhairi; Alwi, Said; Ma'awiyah, Aisyah (Pascasarjana IAIN Lhokseumawe, 2022)
In increasing the understanding of Islamic Religious Education for students at the Al-Aziziyah Samalanga Islamic Religious Education Institute (IAI) Higher Education implements a boarding school education system, so that students are not only focused on deepening the understanding of Islamic Religious Education on campus but they can study more broadly in Islamic boarding schools through the study of turat books taught in Islamic boarding schools. This research is a field research (field research) which is descriptive qualitative. The results of the study show that, First, the administrators of the Al-Aziziyah Samalanga Islamic Institute of Higher Education apply lectures with a boarding school education system by placing students in Islamic boarding schools. Second, in increasing understanding of Islamic religious education, students are more focused on deepening their understanding of Islamic Religious Education in boarding houses by studying turat books taught in Islamic boarding schools. Following the implementation of a comprehensive exam for students before attending the thesis munaqasyah session, the material tested was the recitation of the Qur'an with correct recitation, understanding of Fiqh, Tauhid, Sufism. Third, the obstacles encountered in implementing the boarding school education system at IAI Al-Aziziyah Samalanga are limited time for students, and limited facilities at boarding schools.